Differentiated Instruction as a Catalyst for Educational Transformation: A Meta-Analysis - Muchamad Rizki Eka Setiawan; Raissa Ariadna Putri Josephira; Sari, Desy Kumala; Pri Ariadi Cahya Dinata; Nur Lailatul Rofiah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Differentiated Instruction (DI) has long been implemented to address the diverse learning needs of students. However, exploring its impact on learning outcomes within the framework of modern education has become increasingly important in understanding its effectiveness in the context of 21st-century learning. This meta-analysis aims to investigate the effect of differentiated instruction on students’ learning outcomes. The research method consisted of the stages of identification, screening, and inclusion. The research sample comprised 14 primary studies, producing a total of 41 effect sizes. The analysis revealed a significant effect (1.02; p < 0.05) of DI implementation on students’ learning outcomes. No significant differences in effect size were found based on measured ability, subject, country, sample size, grade level, or Scopus indexing. In terms of contribution, the country variable accounted for a substantial portion of the “weak” and “small” effect size categories. Consequently, the implementation of DI in Asia has been shown to have a significant impact on improving learning outcomes. Furthermore, differentiated instruction exerts a similar influence across all educational levels, suggesting that it should be optimally applied in both primary and secondary schools. Nevertheless, evaluations of psychomotor learning outcomes within the context of differentiated instruction remain limited. This indicates the need for greater attention to the psychomotor domain in future studies, to ensure that the focus extends beyond cognitive and affective abilities.